An evaluation of antibiotic options for the treatment of biothreat pathogens - Meinig, J. Matthew; Nelson, Michelle; Cote, Christopher K.; Emmett, Stevan R.; Harding, Sarah V. (Frontiers in Antibiotics, 2025)
The development of medical countermeasures against pathogens of biodefense concern remains critical to protecting military and public health. This review compares data detailing antibacterial activity and efficacy for a selection of antibiotics evaluated against potential bacterial biothreat pathogens. The human safety and tolerability of these formulations were also considered. This review includes finafloxacin, levofloxacin, delafloxacin, omadacycline, gepotidacin, tebipenem and sulopenem. The selection criteria of these antibiotics were 1) the availability of an oral formulation, 2) the regulatory status (licensed by a regulatory authority or in an advanced stage of development) and 3) the availability of publicly available information on the biodefence pathogens of concern. We hope to highlight approved or advanced clinical candidates that have significant and unique potential in the biodefense space which may be deployed to protect both the public and warfighter against these bacterial infections.